Dampak Penggunaan TIK dalam Pembelajaran terhadap Interaksi Sosial Siswa (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
This study examines the positive impact of ICT use in learning on students' social interactions. The study found that proper ICT integration can enhance collaboration and communication among students, especially through online platforms. Students are able to interact effectively in online learning groups and develop digital communication skills. However, the study also highlights the importance of teacher supervision to prevent negative potentials such as cyberbullying and social isolation. In addition, this study explores the negative impact of ICT use in learning on students' social interactions. The results showed a tendency for decreased face-to-face interaction and verbal communication among students. Excessive use of gadgets and digital platforms can hinder the development of students' social and emotional skills, as well as increase the risk of social isolation and cyberbullying. Furthermore, there is also a complex relationship between ICT use in learning and students' social interactions. The study found that the impact of ICT varies depending on factors such as the age of the students, the type of ICT used, and the quality of implementation. This study highlights the importance of a holistic and balanced approach to the integration of ICT in education that considers both the benefits and risks to students' social development.